2016
DOI: 10.1080/15378020.2016.1185873
|View full text |Cite
|
Sign up to set email alerts
|

Which restaurant should I choose? Herd behavior in the restaurant industry

Abstract: People, in general, follow others' choices or opinions. This phenomenon has been defined as herd behavior. Accordingly, this study utilized the concept of herd behavior, and examined whether restaurant customers follow others' choices or opinions, especially when they choose a restaurant in an unfamiliar place. Two different stimuli were considered "others' choice"-online review ratings and consumers' last minute observations on the crowdedness of the restaurant. By adopting experimental design (3 Crowdedness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 42 publications
4
28
0
3
Order By: Relevance
“…The characteristic of dishes was the most important factor in China [ 24 ], while in the United States the key factors were outstanding quality value and practical value [ 15 , 25 ], and in Delhi (India) the significant deciders were family preferences, habits and perceptions learned in childhood, convenience, and food safety and health [ 26 ]. Other authors have pointed out that word-of-mouth recommendations, external ratings [ 14 ], the degree of crowding, and review ratings [ 13 ] can all affect the choice of eating establishment. Young consumers in Poland and Turkey used different criteria when choosing places to eat out at.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic of dishes was the most important factor in China [ 24 ], while in the United States the key factors were outstanding quality value and practical value [ 15 , 25 ], and in Delhi (India) the significant deciders were family preferences, habits and perceptions learned in childhood, convenience, and food safety and health [ 26 ]. Other authors have pointed out that word-of-mouth recommendations, external ratings [ 14 ], the degree of crowding, and review ratings [ 13 ] can all affect the choice of eating establishment. Young consumers in Poland and Turkey used different criteria when choosing places to eat out at.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have identified the critical factors driving the way consumers choose their eating establishment when eating out. These are food quality, food hygiene and safety, taste, cleanliness, staff behavior, location, reputation, and price [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. However, so far, few studies have examined how consumers go about evaluating the safety level of meals that they eat outside the home.…”
Section: Introductionmentioning
confidence: 99%
“…인지된 위험은 불확실한 상황에서 의사결정에 대한 잠재적 손실에 대한 평가를 의미하며 (Gupta et al, 2004), 인지된 무리 행동은 다른 사람의 의사결정을 모방하 고자 하는 정도로 정의할 수 있다 (Bonabeau, 2004 (Ooi & Tan, 2016;Ryu et al, 2018). 또한, 모바일 내에서 앱 카드를 설치하는 방법이 간단하 고, 개인정보 등록 절차도 간소화되어 쉽고 편리한 서비스로 인 식되고 있다 (Johnson et al, 2018;Slade et al, 2013 (Ding & Li, 2019;Ha et al, 2016;Huang & Chen, 2006;Jiang et al, 2018 (Ajzen, 1991 (Elkaseh et al, 2016;Kim, 2010;Lee et al, 2015;Rivera et al, 2015;Talke & Heidenreich, 2014 (Kwon & Lim, 2012;Yoon et al, 2014), 다양한 인지 요소들에 의해 영향을 받는 혁 신에 대한 개인의 부정적 태도로 확인되었다 (Chen, 2008;Ding & Li, 2019;Huang & Chen, 2006;Raza et al, 2017).…”
Section: A-b-c 모델unclassified
“…모바일 카드를 포 함한 모바일 간편 결제서비스에 대한 선행 연구들을 살펴보면 대 다수의 연구들이 혁신의 특성인 비용과 혜택 측면에서 수용 의도 에 미치는 영향을 살펴보고 있다 (Johnson et al, 2018;Jung et al, 2015;Liébana-Cabanillas et al, 2018). 또한, 단일 차원 에서 모바일 카드에 대한 소비자 태도를 살펴보고 있어 감정과 행 동적 차원에서 모바일 카드에 대한 소비자 태도를 설명하는데 한 계를 가지고 있다 (Sharma et al, 2018;Yoon et al, 2014 (Ding & Li, 2019;Jiang et al, 2018;Sun, 2013 (Ha et al, 2016;Lee & Hong, 2016;Liu et al, 2018) (Ryu et al, 2018;Koenig-Lewis et al, 2015;Song et al, 2016 (Johnson et al, 2018;Ooi & Tan 2016;Slade et al, 2013 (Johnson et al, 2018;Jung et al, 2015;Ooi & Tan 2016;Slade et al, 2013 (Johnson et al, 2018;Jung et al, 2015 (Min & Kim, 2019).…”
unclassified
See 1 more Smart Citation